Agglomeration economies in the presence of an informal sector: the colombian case (2016)
This paper analyzes the relationship between agglomeration economies and wages in the context of a developing country, taking into account the marked presence of the informal sector. Using data from Colombia, we investigate the effect of ag-glomeration economies on formal and informal productivity, inquiring whether the informal sector achieves benefits from agglomeration economies and whether there are differences between the formal and informal sectors in terms of agglomeration returns. We estimate an elasticity of wages with respect to employment density of around -4% for the formal sector, and around 3% for the informal sector. As such, agglomeration has a significantly positive effect on the productivity of the inform sector. The results show that informal workers¿ productivity in a city twice as dense is 2% greater, implying that wages in denser areas are 14% higher than in less dense areas. In contrast, for the formal sector, the results show that productivity in formal workers in a city twice as dense is of around 3% lower, leading such workers to earn 17% less in denser areas. Factors associated with the constraints relative to the creation of formal jobs, a greater labor supply of formal workers, and desamenities very common in big cities in developing countries, could explain these lower agglomeration returns in the formal sector.